Where do they speak from? Positions about the new IMF contractual proposal for ordering sovereign debt restructurings - Manzo, Alejandro Gabriel (2019)
The Sovereign Debt Restructuring (SDR) debate is at the center of the global economic political agenda. In 2014, the IMF issued a new contractual proposal –as an integral part of a set of reforms– to organize these processes but remained outside of the discussions that promoted the creation of an SDR statutory mechanism at the UN, something which marked the existing divisions in the SDR field. Unlike specialized scholars that analyze the limits and potentialities of the IMF contractual proposal in abstracto, this article does it by means of a «game of positions in dispute». This new way of approaching the SDR debate, which starts by making explicit the assumption and interests from where the agents in this field speak, helps to explain why there are not only diverse but directly opposite opinions about the same social fact (the IMF new proposal). It is argued that this proposal improves the existing models of contractual clauses, but it leaves a margin of uncertainty about the correct organization of future restructuring processes: the depth and implications of this uncertainty in the sovereign debt market acquire particularly different meanings according to the worldview of each of the addressed positions.